A Geological Perspective on Climatic Change: Computer Simulation of Ancient Climates - Fawcett, Peter; Barron, Eric (Geoscience Canada, 1991)
Summary The possibility of global warming resulting from the anthropogenic addition of carbon dioxide and other industrial gases into the atmosphere is a topic of much recent concern. Global climate models are used to make predictions for possible future climatic changes, but their ability to simulate climatic states other than the present day is not well constrained. The sedimentary record contains a wealth of information on past global climatic change. From this, we can get a good idea of what past climatic extremes were, and some idea of their underlying causes. If we attempt to simulate the climate of a past time period, we can evaluate the ability of a climate model to represent a climatic state substantially different from the present day. At present, models are not well utilized to reproduce a global climatology for a particular time period. Rather, the models are used for sensitivity experiments. One geologic factor is varied {e.g., geography or C02 level) while all others are held constant. In this way, the effect on the climate of changing that one factor can be tested, and insights into the mechanisms of global change are gained.The results are then compared with the geologic record. Two case studies are given asexamples.